Haydn at Eszterhaza 1766-1790 - Landon, H. C. Robbins 1926-2009 (London Thames and Hudson, 1978)
This volume, the second chronologically of the five which together make up this complete biography of Haydn, deals with the highly important and productive middle years of his career - the period during which he held the post of full Kapellmeister to Prince Nicolaus I Esterhazy. In every aspect of composition Haydn's mature style now came into full flowering, and with the publication and dissemination of his works abroad, his reputation was to become a truly international one.Thanks largely to the survival of the mass of documentary material in the Esterhazy Archives, much of which has been rediscovered and studied only in recent years, it is now possible to paint a detailed picture of daily life in the princely household, and in particular its musical activity: Haydn was responsible not only for the writing of operas, Symphonies, Baryton Trios and other works to satisfy the Prince's requirements, but as Kapellmeister he had also to deal with all the administrative aspects of engaging musicians, supervising the players and seeing to the maintenance of the instruments.
Keywords: Haydn, Joseph -- 1732-1809; Eszterházy family; 18th Century (1701-1800); Composer; Biography; Hungary